Performance analysis of filter sensing board for measuring the battery online impedance - Hossain, M.; Islam, Syed; Park, S. (2017)
© 2016 IEEE. This paper presents the performance analysis of filter sensing board for extracting ac ripple information to estimate the battery impedance for the sinusoidal ripple current charging technique. The charging ac ripple content is extracted from the battery voltage and current by filtering the dc component using an op-amp filter circuit while producing a 90° phase angle in order to transform the a-p frame for calculating the battery impedance. The digital signal processor based board has computational burden due to the many transformations and calculation steps with limited ADC sensing range between 0 to 3 V at 12 bit resolution. Additionally, in the software approach it is observed that the gain and phase angle of sensor output is changing with respect to the AC input ripple frequency. In this paper, we propose a filter sensing circuit board to reduce the transformation and computation burdens for measuring the AC impedance. In this proposed method, the impedance is calculated via a dSPACE interface with a ± 10 V ADC sensing range at 16 bit resolution. This paper also verifies the variation of phase delay between the sensor input and output at different frequencies by using the proposed 16-channel analog filter circuit. A prototype ac load is used as an experimental test bed considering the equivalent battery internal impedance model for measuring the accuracy of the filter sensing board. Finally, the performance of this proposed approach is verified by comparing the experimental result with the simulation and the commercial frequency response analyzer results.